Portfolio Diversification Benefits Using Real Estate Investment Trusts – An Experiment with US Common Stocks, Equity Real Estate Investment Trusts, and Mortgage Real Estate Investment Trusts - Bhuyan, Rafiq; Kuhle, James L.; Al-Deehani, Talla Mohammed; Mahmood, Munir (International Journal of Economics and Financial Issues, 2015)
Using recent data (2002-2012) from the US financial markets, we study the magnitude and benefits of Real Estate Investment Trust (REIT) and common stock in portfolio diversification. In particular, we examine the effects of risk-reduction benefits through diversifying among common stocks via Equity Real Estate Investment Trusts (EREITs) and Mortgage Real Estate Investment Trusts (MREITs). In addition, overall performance measures are calculated and compared among REIT, common stock and mixed-asset portfolios. We observe that investors can benefit from diversification using EREITs but not MREITs. In fact, MREITs turn out to be the worst asset class to be in diversifying portfolio. This conclusion is in contrast with Kuhle (1987) who claims improvement of portfolio risk reduction with MREITs. Our finding, however, is consistent with Hartzell, et al. (1986) and Chen et al. (2005). Finally, even though our data period consists one of the historic collapses of real estate market in the US, it still indicates the equity EREITs still offers diversification benefits. It provides evidence that small investors can use EREITs to diversify their risks. It also offers an opportunity to earn return on real estate investments without investing in real estate properties which may be beyond investor's capacity. Keywords: Portfolio diversification; risk; EREITs; MREITs JEL Classifications: D53; G11; R30